City Government Intervention in Gampong Budgeting: Case Study in Banda Aceh, Indonesia - Ruzan, Muhammad Geubrika; Abdullah, Syukriy; Darwanis, Darwanis (Universitas Syiah Kuala, 2021)
Objective This study aims to explain the intervention of City Government in budgeting in Gampong1 by using agency theory in Banda Aceh.Design/methodology This study is qualitative approach, by collecting data through interviews officials and members of the Gampongs People Representative Council in 5 gam-pongs in Banda Aceh City, Head of sub-district, City Inspectorate, and representatives from the Gampong Community Empowerment Office. Questionnaires were distributed with a total of 363 respondents.Results The results showed that there was an intervention from City Government in the budgeting process in Gampong as a result of the existence of City Government authority as a coach and supervisor of the Gampong government. In addition, the results of the inspec-torate's examination also greatly influenced budgeting in the village the following year.Research Limitation/Implications The lack of literature and previous research on agency problems that occur in the village, the limited competence and lack of cooperation be-tween Keuchik and Tuha Peut Gampong (TPG) when asked for information through inter-views and questionnaires, and The lack of literature on the influence of personal conflict fac-tors (interpersonal) on agency problems.Novelty/Originality The results of this study are expected to be a reference material for academics to examine agency problems in the gampong.